Shaping the Key Competencies for Romanian HEIs’ Teachers in Using Gamification as Innovative Tool in Education: MEDIIA Project Experiments - Marchis, Gabriela (Acta Universitatis Danubius. Œconomica, 2023)
The regular training of teachers on the latest developments in the ICT-assisted education sector is becoming a necessity, generated by the digital revolution and driven by the pandemic crisis. Among the current technological opportunities to improve the quality of the learning process and to make it more flexible in direct correspondence with the training needs and with the personal pace of learning, we find gamification. Improving teaching methods as well as the curriculum, especially by implementing gamification techniques in the teaching process, requires a high level of digital literacy among teachers so that they can (re)design their educational materials in digital format. This was achieved within the Danubius University of Galati (Romania), through the MEDIIA project (project code POCU/320/6/21-122859) carried out between 2019-2021, a project that will be the subject of the case study of this paper.